SNORA72 Activates the Notch1/c-Myc Pathway to Promote Stemness Transformation of Ovarian Cancer Cells - Zhang, Liwen; Ma, Rong; Gao, Mengcong; Zhao, Yanyun; Lv, Xuemei; Zhu, Wenjing; Han, Li; Su, Panpan; Fan, Yue; Yan, Yuanyuan; Zhao, Lin; Ma, Heyao; et al. (Frontiers in Cell and Developmental Biology, 2020)
Cancer stem cells (CSCs) are responsible for the migration and recurrence in the process of cancer progression. Small nucleolar RNAs (snoRNAs) play important roles in tumor development. However, how snoRNAs contributes to regulation of the stemness of ovarian CSCs (OCSCs) remains unclear. In the present study, we found that SNORA72 was significantly upregulated in OVCAR-3 spheroids (OS) and CAOV-3 spheroids (CS) with OCSCs characteristics attained by serum-free culture in suspension of OVCAR-3 (OV) and CAOV-3 (CA) cells. The overexpression of SNORA72 can increase self-renewal abilities, migration abilities in OV and CA cells, and also up-regulated the expression of stemness markers Nanog, Oct4, and CD133. In addition, the ectopic expression of SNORA72 can elevate the mRNA and protein expression levels of Notch1 and c-Myc in the parental cells. And opposite results were observed in SNORA72-silenced OCSCs. In summary, stemness transformation of ovarian cancer cells can be activated by SNORA72 through Notch1/c-Myc pathway. This study introduced a novel therapeutics strategy for improving the treatment efficiencies of ovarian cancer.